Influence of Dielectric Constants of Methanol-Water Mixtures on Formation Constants of Cu(II)-Glycyl-Glycyl-Glycine Complexes - Sondawale, P.J.; Narwade, M.L. (Asian Journal of Chemistry, 2010)
Potentiometric investigation on Cu(II) complexes with glycyl-glycyl-glycine has shown 1:1 and 1:2 complex formation at 0.1 M ionic strength and different percentages of methanol-water mixtures. The data of pK and log k values increased with increasing the percentage of methanol-water mixture.